Probabilistic Thin-Bed Sandstone Reservoirs Delineation in The Montara Formation, Browse Basin, Using Stochastic Inversion and AVF-A (Intercept) Analysis - Arhab, Fadhil; Winardhie, Ignatius Sonny (Scientific Contributions Oil and Gas, 2026)
In the pursuit of net zero-emission targets, restrictions on new oil and gas field discoveries have intensifies the need for enhanced reservoir characterization of secondary resources in mature fields, such as thin-bed reservoirs. However, imaging thin-bed remains challenging due to the limited vertical resolution of conventional seismic data. Advanced methodologies are therefore required to accurately delineate thin-bed sandstone reservoirs and improve reservoir prediction reliability. This study integrates seismic frequency attributes and stochastic seismic inversion to enhance vertical resolution and characterize thin-bed reservoirs within the Montara Formation, Browse Basin. The workflow begins with tuning thickness analysis to identify thin-bed responses, followed by the construction of reflectivity volumes for intercept-based amplitude variation with frequency (AVF-A) analysis and seismic inversion. The results indicate that thin-bed sandstone reservoirs were predominantly deposited during the syn-rift phase and exhibit a Northeast (NE)–Southwest (SW) orientation. These reservoirs are distributed in the eastern well area of the SW region and the western well area of the NE region, with thicknesses of up to 140 m. Probabilistic inversion results indicate reservoir probabilities exceeding 50% within the target zones. These findings demonstrate that integrating seismic frequency attributes with stochastic seismic inversion provides a robust framework for thin-bed bed delineation and reservoir prediction under sub-tuning conditions.